« Quelque chose de rouge » : l’esthétique des tableaux vivants dans Salammbô - Dominique Jullien (Flaubert: Revue Critique et Génétique)
In Salammbô, Flaubert’s writing is generated by a principle analogous to the tableau vivant, pulling the novel in the direction of the visual and spectacular arts. A cultural practice which reached its peak popularity during the Second Empire, the tableau vivant intersects theater, painting, photography, and sculpture, genres and media which Flaubert sought either to emulate or to rival in his writing. It provides a key entry point of engagement with the question of pictorialist writing, as well as an ideal vehicle for Flaubert’s particular vein of Orientalism, defined as a synthesis of beauty and sadism. The question of tableau vivant also links Flaubert’s novel with more recent fiction writing (Roussel, Perec) as well as contemporary performance art.